Pattern of the heart rate performance curve in maximal graded treadmill running from 1100 healthy 18–65 Years old men and women: the 4HAIE study - Birnbaumer, Philipp; Dostal, Tomas; Cipryan, Lukas; Hofmann, Peter (Frontiers in Physiology, 2023)
The heart rate performance curve (HRPC) in maximal incremental cycle ergometer exercise was shown to be neither linear nor uniform. Three different patterns (downward, linear and inverse) have been prescribed with some implications for exercise prescription, but no data are available for running tests. This study investigated the deflection of the HRPC in maximal graded treadmill tests (GXT) of the 4HAIE study. Additional to maximal values, the first and second ventilatory thresholds as well as the degree and the direction of the HRPC deflection (kHR) were determined from 1100 individuals (489 women) GXTs. HRPC deflection was categorized as downward (kHR < -0.1), linear (-0.1 ≤ kHR ≤ 0.1) or inverse (kHR > 0.1) curves. Four (even split) age- and two (median split) performance-groups were used to investigate the effects of age and performance on the distribution of regular (= downward deflection) and non-regular (= linear or inverse course) HR curves for male and female subjects. Men (age: 36.8 ± 11.9 yrs, BMI: 25.0 ± 3.3 kg.m-2, V̇O2max: 46.4 ± 9.4 ml.min-1.kg-1) and women (age: 36.2 ± 11.9 yrs, BMI: 23.3 ± 3.7 kg.m-2, V̇O2max: 37.4 ± 7.8 ml.min-1.kg-1) presented 556 / 449 (91 / 92 %) downward deflecting, 10 / 8 (2 / 2 %) linear and 45 / 32 (7 / 6 %) inverse HRPC´s. Chi-squared analysis revealed a significantly higher number of non-regular HRPC´s in the low-performance group and with increasing age. Binary logistic regression revealed that the odds ratio (OR) to show a non-regular HRPC is significantly affected by maximum performance (OR = 0.840, 95 % CI = 0.754 - 0.936, p = 0.002) and age (OR = 1.042, 95 % CI = 1.020 - 1.064, p < 0.001) but not sex. Like in cycle ergometer exercise, three different patterns for the HRPC were identified from the maximal graded treadmill exercise with the highest frequency of regular downward deflecting curves. Older subjects and subjects with a lower performance level had a higher probability to show a non-regular linear or inverted curve which needs to be considered for exercise prescription.